The influence of marketing mix on purchase decisions - Akhmalia, Dina Garnida (Jurnal Inovasi Ekonomi, 2023)
This study investigates the impact of the marketing mix—product, price, place, and promotion—on purchasing decisions at Warung Ketan Susu Tasikmalaya. Using a quantitative approach, data from 100 consumers were analyzed through multiple linear regression. Results show that product quality positively influences purchases, while higher prices deter them. Location convenience and effective promotions also play significant roles. These findings offer actionable insights for enhancing business strategies and driving sales in competitive markets.